MODEL PEMBELAJARAN INKUIRI TERINTERNALISASI AYAT-AYAT AL-QUR’AN UNTUK MENINGKATKAN PEMAHAMAN KONSEP LARUTAN PENYANGGA DAN KARAKTER ISLAMI SISWA - Safrijal Safrijal (Lantanida Journal, 2015)
The research was motivated by rise of student behavior who have not reflected noble character and still rarity of teacher internalize the chemical in the verses of the Qur'an. This research aim to determine the application of inquiry learning model internalized the verses of the Qur'an on the concept of buffer solution and get an idea of the level of students 'understanding of concepts, and obtain a description of Islamic character student responses on the implementation of inquiry learning model internalized the verses of the Qur' 's. The research method used was a quasi-experimental design with one group pretest posttest design. Sampling technique is purposive sampling. The subject in this study is XIIA2 grader who amounted to 30 people, consisting of 8 men and 22 women. The data was collected using a pretest and posttest for understanding concepts, observation sheet to observe Islamic character, LKS for inquiry learning activities and a questionnaire to determine students' responses to the implementation of inquiry learning model internalized the verses of the Qur'an. Data processing is performed with N-gain test pretest and posttest values of the individual students, the value of N-gain of 0.80 which is higher categories were 19 students (63.33%) and N-gain value of 0.66 was considered a total of 11 students (36.67%), and obtained an overall average of the N-average gain of 0.78 is considered high. Based on the results of t-test (paired sample test) obtained -thitung